Awareness on thalassemia and opinion of carrier screening among young women from selected undergraduate colleges of udupi district - Rishmitha; Sulochana Badagabettu; Archana M V; Vani Lakshmi R; Jomon C U (Elsevier, 2022)
Introduction: Hemoglobinopathies are inherited disorders of red blood cells that poses significant cause of morbidity and mortality, impose a heavy burden on family. The study aims to assess the awareness of Thalassemia, and its willingness to screen among young women from Udupi district. Methods: A descriptive cross-sectional survey design was employed to assess the awareness on Thalassemia among young women belonging to the age group of 18-24 years from selected undergraduate institutions of the Udupi district. The study used descriptive statistics, data visualization methods and chi-square tests. Results: Among the 389 participants, 3(0.8%) of the participants reported Thalassemia in their families. Also, 28(7.2%) of the participants have a history of consanguineous marriage. 273 (70%) participants reported Thalassemia is a lifetime condition, whereas 284(73%) believed that consanguinity does not increase the Thalassemia incidence. According to 275(70%) respondents, premarital screening is not essential to rule out Thalassemia.The readiness of young women to screen for carrier status was estimated to be 57(15%), While 101(27%) were unwilling to screen, While 221 (58%) were unsure about screening for carrier status. Based on Pearson's Chi-Squared test, there was association between following variables: Age and Thalassemia awearness, (χ2 (4) = 13.749, p < 0.008), Education and Thalassemia awearness (χ2 (4) = 10.864, p < 0.028), knowledge score and family income (χ2 (8) = 21.100, p < 0.007). Conclusion: The premise suggests a lack of awareness of Thalassemia disorder among young women, this calls for an urgent need to revise the Thalassemia control programme.